STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA PETANI STROBERI DI DESA PANCASARI - Widiawati, Ni Luh; Yuniati, Ketut; Yasa, I Kadek Abdhi (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Communication is a person's interaction with other people to provide a public, personal or business message in order to achieve the desired goals. Likewise, strawberry farmers in Pancasari Village want to increase sales by implementing marketing communication strategies. Many farmers sell their crops only to collectors, making a small profit compared to the cost of maintaining strawberry trees. Thus, this research aims to find out how the marketing communication strategies used by strawberry farmers are in increasing sales factors and obstacles in increasing sales as well as implementing marketing communication strategies in increasing strawberry sales results in Pancasari village. This research uses qualitative research methods, with data collection methods of observation, interviews and document study. The data analysis used is data collection, data reduction and drawing conclusions. The theories used in this research are Marketing Mix theory, Plan theory, S-O-R theory. The research results show that the marketing communication strategy carried out by strawberry farmers to increase sales uses a marketing mix strategy which consists of four elements, namely Place, Product, Price and Promotion. The obstacles encountered in achieving the strategy are internal barriers from farmers due to knowledge and motivation. Meanwhile, external obstacles start from fruit supplies and space supplies (parking lots, rest areas, photo spots). The perceived implications of the marketing communication strategy carried out by farmers can increase sales and gain more profits than before and from Pancasari Village which has experienced increased tourism development since the opening of strawberry picking tourism by strawberry farmers in Pancasari Village.